The Correlation between Reading Comprehension and Students’ Ability in Answering Cloze Test of The Seventh Grade Students at SMP N 1 Kalipuro Banyuwangi in The 2014/2015 Academic Year - Piyani, Piyani (LUNAR, 2017)
Reading comprehension is a process of comprehending meaning from a text. In reading process, especially about English text, the readers can enrich their vocabulary and their knowledge. Reading also can increase their experience because the reader know about a new information which do not know before. Reading comprehension is important for student. Because reading comprehension can give them some idea for written. In reading comprehension process they imagine about the contain of the text and they can retell about the text in form of written. In this thesis, the researcher held a research about the correlation study between reading comprehension and studentsÃ¢â‚¬â„¢ ability in answering cloze test of the seventh grade students at SMPN 1 Kalipuro Banyuwangi in the 2014/2015 Academic Year. The objective of this research is to investigate correlation between reading comprehension and studentsÃ¢â‚¬â„¢ ability in answering cloze test. the data of the research collected by test, the researcher used essay test to collect score of reading comprehension and cloze test. The determination of the respondent Population of this research was taken from the Seventh years students at SMPN 1 Kalipuro Banyuwangi in the 2014/2015 academic year. They are 37 students as the research sample which was taken by using cluster random sampling. Based on the result of the data analysis of product moment formula, it can be known the statistical value of correlation coefficient is higher than the Ã¢â‚¬Å“rÃ¢â‚¬Â table. That is 0,59 > 0,325. It indicated that there was correlation between reading comprehension and studentsÃ¢â‚¬â„¢ ability in answering cloze test. And the level of correlation between reading comprehension and studentsÃ¢â‚¬â„¢ ability base on the result of statistical formula in answering cloze test was enough